Anterior intercostal artery perforator flap for immediate reconstruction following breast conservation surgery. Issue 1 (21st March 2022) - Adler, Neta; Carmon, Einat; Chapchay, Katya; Billig, Allan
Abstract: Introduction: Oncoplastic breast surgery following breast conservation surgery (BCS) utilizes aesthetic breast reduction techniques, and these reconstructions entail either volume displacement or volume replacement depending on the size and location of the excised tumor. The anterior Intercostal flap (AICAP) for immediate reconstruction after BCS is scarcely described in the literature. In this study, we present our experience with the Anterior Intercoastal Artery Perforator flap in 16 patients with small breast sizes. Patients and Methods: Sixteen patients underwent lumpectomy followed by immediate reconstruction with Anterior ICAP flap between 2019 and 2021 at Hadassah University Hospital. Median age was 49 (range 28–67). Breast cup size, lumpectomy to breast size ration, defect measurements and location are provided. Flap design and flap in‐setting was planned and executed according to the size and location of the defect determined at the time of surgery. Surgical technique is described. Diagram of proposed reconstruction according to defect location is proposed. Results: Flap dimensions clinically matched the defect size or were slightly larger due to anticipated shrinkage of tissue post radiation with mean of 5.4 × 3.9 × 3.75 cm (range of 2.5–13 × 2–13.2 × 0.8–4.5 cm). Complications, namely one seroma and one mild infection, were seen in two patients. Median follow up was 3 months after completion of radiation. All reconstructions were satisfactory by both surgeon and patient at last post‐operative follow‐up visit. Conclusion: The anterior ICAP flap is an important addition to the armamentarium of immediate reconstruction options after BCS, particularly in patients smaller size breast sizes.